Numerical Analysis of Fluid Flow on Wall Cylinder Circular with K-ε Modeling for a High Reynolds Rate - M. Yasep Setiawan; Wawan Purwanto; Wanda Afnison; Nuzul Hidayat (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2019)
This study discusses the numerical study of two-dimensional analysis of flow through circular cylinders. The original physical information entered in the equation governing most of the modeling is transferred into a numerical solution. Fluid flow on two-dimensional circular cylinder wall using high Reynolds k-ε modeling (Re = 106), Here we will do 3 modeling first oder upwind, second order upwind and third order MUSCL by using k-ε standard. The general procedure for this research is formulated in detail for allocations in the dynamic analysis of fluid computing. The results of this study suggest that MUSCL's third order modeling gives more accurate results better than other models.